The 2025 Fitness Trend: Why Yoga and Pilates Have Become the Preferred Choice - Martini, Titin; Hikmah, Hikmah (Oshada, 2025)
In recent years, there has been a paradigm shift in exercise practice, from a focus on physical strength to a more holistic and reflective approach. This study aims to explore why Yoga and Pilates are the main choices in exercise trends in 2025, especially in Indonesia. Using a qualitative phenomenological approach, eight informants who regularly participate in Yoga or Pilates were interviewed in depth. The results show five main themes: (1) the search for holistic health that includes physical and mental balance; (2) the need for calm amidst the pressures of modern life; (3) flexibility in time, place, and access thanks to digital technology; (4) the influence of social media and online communities as agents of promotion and motivation; and (5) personal transformation and spiritual meaning felt by participants. These findings indicate that Yoga and Pilates are not just physical exercise, but also transformative, reflective, and inclusive self-care practices. The implications of this study point to the importance of supporting widespread access to mindfulness-based exercise, as well as the need for policies that bridge the gap in community participation.